Idealism and Realism in the Study of the Philosophy of Islamic Family Law - Noni Kensiwi; Fiqi Restu Subekti (Journal of Legal, Political, and Humanistic Inquiry, 2025)
The philosophy of Islamic family law is characterized by a persistent tension between normative Idealism and contextual Realism. Idealism emphasizes fidelity to divine texts, moral universality, and transcendent legal purposes, while Realism prioritizes empirical conditions, social effectiveness, and institutional implementation. This article examines the conceptual foundations of both paradigms and analyzes their practical implications for marriage, divorce, and inheritance within contemporary Muslim societies. Employing a qualitative normative methodology based on literature review, philosophical analysis, and comparative socio-legal studies, the article demonstrates that neither Idealism nor Realism alone can adequately address the complexity of modern family law challenges. The study argues that a maqasidiyah-oriented framework offers an effective epistemological synthesis by integrating teleological reasoning with contextual sensitivity. By treating the objectives of the Sharia as the primary normative reference while incorporating empirical data as interpretive guidance, maqasidiyah reconciles textual authority with social reality. The article concludes that this synthesis enables adaptive and accountable ijtihad, strengthens substantive justice, and enhances the relevance of Islamic family law in plural and evolving legal environments.